History Of Issues Of Construction Of Modern Residential Buildings In The Years Of Independence - F.Ochilov (Academia One Publishing, 2024)
This article is devoted to the history of the current issues of building modern residential buildings in Uzbekistan during the years of independence
Keywords: Construction; house; housing